Pengaruh Persepsi Pengurus Gereja Terhadap Penyusunan Laporan Keuangan - Jeraki Tabaru, Januarius; Setiawan, Aris (Program Studi Akuntansi Universitas Panca Bhakti, 2025)
This research is motivated by the problems faced by most churches that have not made financial reports, while financial reports are important as a form of accountability for people's funds and as a basis for church accountability. The purpose of this study was to test and analyze the effect of church management perceptions on the preparation of financial reports and to determine the design of the preparation of church financial reports based on ISAK 35. The population in this study were parish priests and treasurers involved in preparing financial reports from 26 parish churches in Sanggau Regency. The sampling technique used purposive sampling method and data collection using questionnaires to 52 respondents. The research was conducted with a mixed method approach to quantitative and qualitative research. Data analysis techniques using simple linear regression and ISAK 35. The results showed that the variable perception of church administrators partially had a significant influence on the variable preparation of financial statements. Based on the analysis of financial data related to the Kuala Dua Good Shepherd Parish Church, the results show that the design of the preparation of church financial reports is not fully in accordance with generally accepted standards due to the lack of research data that researchers get so that it is unable to show the overall financial condition of the church. This research can be a reference for further research that leads to church financial management by implementing the design of church financial reports based on generally accepted standards.